2008
DOI: 10.1002/nau.20643
|View full text |Cite
|
Sign up to set email alerts
|

Does sensory bladder function during cystometry differ from that in daily life? A study in incontinent women

Abstract: During conventional cystometry the patients with different types of incontinence experience the degrees of desire to void at larger volumes than in daily life. Sensation related symptoms will thus be more accurately studied with the SR-BD than with cystometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…Also, the laboratory situation may cause a variation in the patient's usual “lower urinary tract behaviour”. This means that volumes and urodynamic filling sensations and capacity have to be weighed against the information from the patients' voiding diary [14]. …”
Section: Normal Values Reliability and Diagnostic Performancementioning
confidence: 99%
“…Also, the laboratory situation may cause a variation in the patient's usual “lower urinary tract behaviour”. This means that volumes and urodynamic filling sensations and capacity have to be weighed against the information from the patients' voiding diary [14]. …”
Section: Normal Values Reliability and Diagnostic Performancementioning
confidence: 99%
“…However, data from a sensation-related voiding diary, where every void and leakage is reported with the desire that was experienced at the same time, show a correlation with data from urodynamic tests (De Wachter & Wyndaele 2003b, Naoemova et al . 2009).…”
Section: Part 2: Experiencing Sensation Related To the Urinary Bladdermentioning
confidence: 88%
“…In current practice, it is important to determine the changes in the anatomical structures with their functional interactions in the diagnosis and treatment planning of UI (8). The measurement of the intensity of desire for micturition has attracted great interest for the determination of the severity of symptoms and the evaluation of treatment results in many of lower urinary tract disorders (9). In patients with overactive bladder (OAB), the developement of an assessment scale and the evaluation of urgency, which is the most common complaint of OAB patients, is particularly important (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that no significant difference was found between the daily voiding accounts of MUI and UUI groups (3). Furthermore, additional studies are present in the previous literature (9,17). On the other hand, when we looked at the urodynamic findings regarding the frequency of DO Currently, the nomograms such as Abram--Griffits and Schafer, and the indexes such as Bladder Outlet Obstruction Index and Bladder Contractility Index are used to objectively evaluate bladder emptying (19).…”
Section: Discussionmentioning
confidence: 99%